2022
DOI: 10.3389/fendo.2021.792795
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bilirubin Level Is Increased in Metabolically Healthy Obesity

Abstract: ObjectivesBilirubin is a biochemical substance with metabolic benefits. The objective of this research was to elucidate the association between serum bilirubin levels and metabolic alterations in different obesity phenotypes.MethodsIn total, 1,042 drug-naive participants were included in the study. Of them, 541 were obese patients and 501 were age-matched and sex-matched healthy control subjects. The obese patients were divided into metabolically healthy obesity (MHO) group and metabolically unhealthy obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Specifically, in the logistic regression analysis model, patients with a higher TB level had a lower TG level, those with a higher CB level had a lower TC level, and those with a higher UCB level had a higher HDL-C level; In the linear regression model, CB, but not UCB levels, were negatively correlated with the FBG level. The differences were also observed in the general population and schizophrenia patients in previous cross-sectional and prospective studies [ 58 , 59 ]. Bilirubin is a lipid-soluble substance, and different types of bilirubin bind differently to albumin.…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, in the logistic regression analysis model, patients with a higher TB level had a lower TG level, those with a higher CB level had a lower TC level, and those with a higher UCB level had a higher HDL-C level; In the linear regression model, CB, but not UCB levels, were negatively correlated with the FBG level. The differences were also observed in the general population and schizophrenia patients in previous cross-sectional and prospective studies [ 58 , 59 ]. Bilirubin is a lipid-soluble substance, and different types of bilirubin bind differently to albumin.…”
Section: Discussionsupporting
confidence: 69%
“…Currently, the results of research on the association between bilirubin and lipid levels are still inconsistent. Fu et al [ 22 ] reported that TBil and DBil levels were inversely related to TC and TG levels, while no significant correlation between IBil and the two lipid levels was observed. In the study by Seyed et al [ 23 ], compared to men with low levels of bilirubin, those with mildly elevated bilirubin levels showed TG levels that were approximately 0.55 mmol/L lower.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bilirubin behaves as a signaling molecule acting on various nuclear and cytoplasmic receptors [ 3 , 4 ]. Apart from beneficial effects on atherosclerotic diseases [ 29 ], mildly elevated serum bilirubin concentrations seem to protect against the development of obesity, metabolic syndrome [ 7 , 8 , 9 ] as well as diabetes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this association with abnormal glucose tolerance tests was reported as early as 1996 [ 10 ]. Numerous clinical studies reporting lower serum/plasma bilirubin concentrations with the risk of diabetes (and its complications) were published in the following decade, as summarized in 2012 [ 11 ], as well as being confirmed in more recent studies [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 93%